Cold temperature shock tetraploidization of striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) with different of temperature and age of zygote - Alfis Syahril; Odang Carman; Dinar Tri Soelistyowati (Jurnal Iktiologi Indonesia, 2020)
Striped catfish (Pangasianodon hypophthalmus) has a relatively slow growth, so the operational cost of production is high and incomparable with the selling price, thus makes the cultivation of striped catfish is inefficient. Genetic quality improvement through polyploidization is to produce sterile triploid fish (3n) that can overcome this problem. The provision of triploid fish is more efficient through tetraploidization. Tetraploidization in striped catfish using cold shock treatment has never been done before. The purpose of this study was to determine the optimum tetra-ploidization condition using cold shock with temperature and different age of zygote in striped catfish. A completely randomized factorial design with two treatments i.e. three level of temperatures (8oC, 12°C, 16oC ) and two different ages of zygote (29 and 31 minutes after fertilisation-maf) and three replications was used. In addition, a control without applying temperature shock treatment was performed, Soaking process was conducted for 30 minutes. Tetraploid identification was done by calculating the maximum total of nucleoli per cell that was confirmed by calculating the total of chromosome. The results showed that the degree of hatching rate and abnormalities has a significantly different effect (P <0.05). Number of nucleoli per cell was 4 and chromosomes was 112 (4n=112) for tetraploid), whereas for diploid fish the maximum number of nucleoli per cell was 2 and the number of chromosomes was 56 (2n=56). The highest tetraploid percentage was obtained at a treatment of 12oC at age of zygote 29 maf. Thus, the optimum condition of tetraploidization in striped catfish is using cold shock treatment of 12oC with the age of zygote of 29 maf. Abstrak Ikan patin siam (Pangasianodon hypophthalmus) memiliki pertumbuhan yang relatif lambat sehingga biaya operasional produksi tinggi tidak sebanding dengan rendahnya harga jual yang mengakibatkan budidaya ikan patin siam tidak efisien. Perbaikan mutu genetik melalui poliploidisasi yaitu untuk menghasilkan ikan triploid (3n) yang bersifat steril dapat mengatasi masalah tersebut. Penyediaan ikan triploid lebih efisien melalui tetraploidisasi. Tetraploidisasi pada ikan patin siam menggunakan perlakuan kejutan dingin belum pernah dilakukan sebelumnya. Penelitian ini bertujuan untuk menentukan kondisi optimum tetraploidisasi menggunakan kejutan dingin dengan suhu dan umur zigot berbeda pada ikan patin siam. Rancangan percobaan pada penelitian ini adalah Rancangan Acak Lengkap faktorial dengan dua faktor dan tiga ulangan, yaitu suhu 8oC, 12oC,16oC dan umur zigot 29 dan 31 msf (menit setelah fertilisasi) dengan perendaman selama 30 menit dan satu perlakuan kontrol (tanpa pemberian kejutan suhu). Identifikasi tetraploid dilakukan dengan menghitung jumlah maksimum nukleolus per sel yang dikonfirmasi dengan penghitungan jumlah kromosom. Hasil penelitian menunjukkan bahwa derajat penetasan dan abnormalitas berbeda nyata (P<0,05). Hasil pengamatan pada ikan tetraploid diperoleh jumlah maksimum nukleoli adalah 4 per sel dan jumlah kromosom yaitu 112 (4n=112), sedangkan pada ikan diploid adalah 2 per sel dan jumlah kromosom yaitu 56 (2n=56). Persentase tetraploid tertinggi diperoleh pada perlakuan suhu 12oC umur zigot 29 msf. Disimpulkan bahwa kondisi optimum tetraploidisasi pada ikan patin siam menggunakan kejutan dingin pada suhu 12oC dengan umur zigot 29 msf.